Perpetration and Victimization of Intimate Partner Violence Among Young Men and Women in Dar es Salaam, Tanzania. Issue 16 (August 2018) - Mulawa, Marta; Kajula, Lusajo J.; Yamanis, Thespina J.; Balvanz, Peter; Kilonzo, Mrema N.; Maman, Suzanne
We describe and compare the baseline rates of victimization and perpetration of three forms of intimate partner violence (IPV)—psychological, physical, and sexual—among sexually active men ( n = 1, 113) and women ( n = 226) enrolled in an ongoing cluster-randomized HIV and gender-based violence prevention trial in Dar es Salaam, Tanzania. IPV was measured using a modified version of the World Health Organization Violence Against Women instrument. We assess the degree to which men and women report overlapping forms of IPV victimization and perpetration. Sociodemographic and other factors associated with increased risk of victimization and perpetration of IPV are examined. Within the last 12 months, 34.8% of men and 35.8% of women reported any form of IPV victimization. Men were more likely than women to report perpetrating IPV (27.6% vs. 14.6%, respectively). We also found high rates of co-occurrence of IPV victimization and perpetration with 69.7% of male perpetrators and 81.8% of female perpetrators also reporting victimization during the last year. Among men, having ever consumed alcohol and experiencing childhood violence were associated with increased risk of most forms of IPV. Younger women were more likely to report perpetrating IPV than older women. We found evidence of gender symmetry with regard to most forms of IPV victimization, but men reported higher rates of IPV perpetration than women. Given the substantial overlap between victimization and perpetration reported, our findings suggest that IPV may be bidirectional within relationships in this setting and warrant further investigation. Implications for interventions are discussed.